Multimodality Treatment Including Triplet Regimen as First-Line Chemotherapy May Improve Prognosis of Serum AFP-Elevated Gastric Cancer with Liver Metastasis - Yakun Wang; Lin Shen; Ming Lu; Zhi Ji; Xiaotian Zhang (Gastroenterology Research and Practice)
Serum α-fetoprotein- (AFP-) elevated gastric cancer is a rare tumor that has a poor prognosis due to high incidence of liver metastasis. This study sought to investigate the optimal treatment modality. A total of 319 gastric cancer patients with liver metastasis (GCLM) whose serum AFP levels were tested before treatment were enrolled in this study. They were classified as the serum AFP ≥ 20 ng/ml group (n=74) and the AFP < 20 ng/ml group (n=245). Median OS of the AFP < 20 ng/ml group was significantly longer than that of the AFP ≥ 20 ng/ml group (15.7 m versus 10.9 m, P=0.004). ORR of first-line chemotherapy was 43.3% and 56.1% of the two groups, respectively (P=0.024). Of patients who received doublet regimen, ORR of the AFP ≥ 20 ng/ml group was significantly lower (38.2 versus 56.9%, P=0.013), while in those received triplet regimens, ORR between two groups was similar (66.7% versus 66.7%, P=0.676). Moreover, for patients of the AFP ≥ 20 ng/ml group, those who reached PR had a longer survival period (15.4 m versus 9.4 m, P=0.017), and combined with local treatment for liver metastasis also seemed to improve prognosis (19.2 m versus 8.4 m, P=0.003). In conclusion, serum AFP-elevated GCLM had a poorer prognosis. Multimodality treatment including aggressive first-line chemotherapy with triplet regimen may be needed when treating them.